2001
DOI: 10.4319/lo.2001.46.1.0095
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and vertical complexity of attached and free‐living bacteria of the eastern Mediterranean Sea, determined by 16S rDNA and 16S rRNA fingerprints

Abstract: The community structure of attached and free-living bacteria in the Aegean Sea (eastern Mediterranean Sea) was analyzed with use of terminal-restriction fragment length polymorphism (T-RFLP) fingerprinting. Since the Aegean Sea is characterized by rather small temperature fluctuations between surface and deep-water layers, it represents an ideal study site to determine the variations in the community structure of bacteria with depth, since environmental factors other than temperature are likely to determine de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
148
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(174 citation statements)
references
References 34 publications
22
148
1
1
Order By: Relevance
“…Peaks that were located closer than 2 bp from each other were binned. We used the limit of 2 bp for all fragment sizes (Moeseneder et al 2001). …”
Section: Methodsmentioning
confidence: 99%
“…Peaks that were located closer than 2 bp from each other were binned. We used the limit of 2 bp for all fragment sizes (Moeseneder et al 2001). …”
Section: Methodsmentioning
confidence: 99%
“…The decrease in richness in the anoxic part of the Baltic might be due to the limited groups of bacteria that could thrive without oxygen and use the available mix of electron donors and acceptors. Various vertical major communities along the water column have been observed in many aquatic ecosystems, ranging from open oceans to small lakes (Moeseneder et al, 2001;Dominik and Hö fle, 2002;Treusch et al, 2009). In comparison with large ocean basins, the vertical extent of the central Baltic is more than an order of magnitude less.…”
Section: Vertical Community Structure Of Bacterioplankton In the Gotlmentioning
confidence: 99%
“…The discrepancy between RNA-and DNA-based studies of surface bacterioplankton has been observed in marine and freshwater ecosystems (Moeseneder et al, 2001;Troussellier et al, 2002;Lami et al, 2009;Treusch et al, 2009;Logue and Lindströ m, 2010). Most studies explained this phenomenon by hypothesis 2, that is, some of the present bacteria are not as active as others due to the high dynamics of surface water in terms of the diurnal light cycle.…”
Section: Utility Of Cordaf For the Understanding Of Bacterial Communimentioning
confidence: 99%
“…While less specific than direct cell counts or quantitative PCR estimates, T-RFLP analyses have been used to identify differences between prokaryotic communities in response to various environmental factors. For example, Moeseneder et al (2001) used T-RFLP to compare attached and free-living bacterial communities of the eastern Mediterranean Sea, while González and coworkers (2000) used this method to fingerprint bacterioplankton communities associated with an eddy-induced oceanic algal bloom in the North Atlantic Ocean. Here we use NMS, T-RFLP, rDNA cloning, and phylogenetic analyses to identify and characterize bacterioplankton community shifts from monthly surface and 200-m samples collected at the BATS site between 1992 and 2002.…”
Section: Acknowledgmentsmentioning
confidence: 99%